Evaluation of the choroidal features in pachychoroid spectrum diseases by optical coherence tomography and optical coherence tomography angiography. Issue 1 (January 2021) - Demirel, Sibel; Değirmenci, Mehmet Fatih Kağan; Batıoğlu, Figen; Özmert, Emin
Purpose: To evaluate choroidal area, stroma/lumen ratio, choriocapillaris vessel density, and choriocapillaris flow area in eyes with central serous chorioretinopathy, uncomplicated pachychoroid, and pachychoroid pigment epitheliopathy using enhanced depth imaging-optical coherence tomography and optical coherence tomography angiography. Materials and Methods: This retrospective study analyzed enhanced depth imaging-optical coherence tomography and optical coherence tomography angiography scans of 142 eyes of 92 patients with central serous chorioretinopathy, uncomplicated pachychoroid, and pachychoroid pigment epitheliopathy. The choroidal area and stroma/lumen ratio were measured by binarization of enhanced depth imaging-optical coherence tomography images. Choriocapillaris vessel density and choriocapillaris flow area were measured at the choriocapillaris level by manual segmentation of optical coherence tomography angiography scans. Results: The mean stroma/lumen ratio results were 0.361, 0.345, and 0.354 in central serous chorioretinopathy, uncomplicated pachychoroid, and pachychoroid pigment epitheliopathy groups, respectively ( p > 0.05). The mean whole image choriocapillaris vessel density in uncomplicated pachychoroid group was higher compared with central serous chorioretinopathy and pachychoroid pigment epitheliopathy groups ( p < 0.0001). The mean foveal, parafoveal, and perifoveal choriocapillaris vessel densities were lower in central serous chorioretinopathy group than in uncomplicated pachychoroid group ( p < 0.0001). The mean choriocapillaris flow area was lower in central serous chorioretinopathy group than in uncomplicated pachychoroid and pachychoroid pigment epitheliopathy groups ( p < 0.0001 and p = 0.01, respectively). Conclusion: Our findings suggest that both choroidal vessels and stroma are equally involved in central serous chorioretinopathy, uncomplicated pachychoroid, and pachychoroid pigment epitheliopathy. The choriocapillaris segment seems to be more affected in central serous chorioretinopathy compared to uncomplicated pachychoroid and pachychoroid pigment epitheliopathy. However, the reduced optical coherence tomography angiography signal in central serous chorioretinopathy group could be due to shadowing artifact or choriocapillaris hypoperfusion and further studies with higher quality imaging tools are needed.